Vietnam: A Guide to Economic and Political Developments - Jeffries, Ian (Routledge, 2020)
Winning the Vietnam War proved easier than winning the peace. Since 1975, the reunited country has faced the problem of how a poorer, planned economy in which state ownership and control could successfully absorb a more advanced, capitalist economy. In addition, the collapse of communism and the end of the Cold War heralded a new age in Vietnam’s internal and external relations.